CHI '02 Extended Abstracts on Human Factors in Computing Systems 2002
DOI: 10.1145/506443.506578
|View full text |Cite
|
Sign up to set email alerts
|

A picture says more than a thousand words

Abstract: Virtual re-embedding, i.e. adding social cues to a website, has been suggested as a possible strategy to increase consumer trust in online-vendors. Numerous online retailers meanwhile incorporate this strategy, for example by adding photographs and names of customer service agents or by creating chat and callback opportunities. Yet, little is known about the effectiveness of virtual reembedding. The present study examined the effectiveness of a comparably simple strategy, the inclusion of photograph in an e-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…In the case of electronic commerce, this may be accomplished through the design of the website, as user response can be manipulated by modifying visual elements of the design [43]. For example, visual content such as photos of people [3] or human pictures [8], [10] can be included in the design to improve social presence in a website. Similarly, country-related content in pictures may be able to increase country presence in the foreign online store.…”
Section: Theoretical Framworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of electronic commerce, this may be accomplished through the design of the website, as user response can be manipulated by modifying visual elements of the design [43]. For example, visual content such as photos of people [3] or human pictures [8], [10] can be included in the design to improve social presence in a website. Similarly, country-related content in pictures may be able to increase country presence in the foreign online store.…”
Section: Theoretical Framworkmentioning
confidence: 99%
“…In order to improve the perception of closeness with the online store, research on consumer behavior in electronic commerce has looked into the concept of presence [3]- [5]. The sense of presence, that is, the sense of being psychologically transported to another place or with other people through a technological medium [6], can help reduce the perception of distance [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, unlike the first experiment that provided no supporting evidence in favor of H cog (see Table 2), experiment 2 did provide support for our hypothesis on cognitive trust, instead (see Table 4). Including photos in online shops influences trust building positively [24] Information elements typical of social media able to foster not only affective-but also cognitive-trust building Showing photos of employees increases customers' trust towards online-bank website [30].…”
Section: Cognitive Trustmentioning
confidence: 99%
“…Riegelsbeirger et al [24] showed that including photos in online shops might positively affect trust building, as far the pictures match the overall site's design and the vendor's brand. Steinbrueck et al [30] observed that showing the photos of employees might increase customers' trust towards an onlinebank website.…”
Section: Cognitive Trustmentioning
confidence: 99%